Household's willingness-to-pay estimation for safe drinking water: a case study in Vietnam - Khuc, Quy Van, author; Loomis, John B., advisor; Kling, Robert, committee member; Goemans, Christopher G., committee member (Colorado State University. Libraries, 2013)
This thesis explores consumer behavior of households for drinking water by surveying and analyzing 235 households (HHs) in Hanoi and Hai Duong in the North of Vietnam, and Ho Chi Minh in South of Vietnam. Two classical methods have been employed, Contingent valuation method (CVM) and averting behavior method (ABM). Binary logit regression can help to identify internal and external factors influencing the decision of whether or not to pay for clean drinking water. In addition, the linear regression method allows to explore and to quantify the magnitude of relationship between the dependent variable and independent variables. Generally, about half of the households surveyed are willing to pay for better drinking water. Most of them are HHs living in two major cities, Hanoi and Ho Chi Minh City. On average for all of the sampled households, the value of willingness-to-pay makes up small percentage of household income, just 0.247% of total household income. The decision to pay for water depends on both internal factors: the level of education and awareness, as well as external factors: living conditions and existing water source. For those households that are willing to pay to get clean water services, income, and current status of water resources are strong variables. In addition, those households that are actively looking for information and learning related to water often pay a fee for water use. Different measures are practiced by HH's to prevent diseases caused by possible polluted drinking water. Of the five averting activities, boiling water is HHs' priority in rural areas due to low cost while buying bottled water is HH's choice in the city because of the convenience. Young people tend to use bottled water more than old people. Using a water filter increases amount of money they would be willing to pay for clean water, while income and habitat of using drinking water are also strong factors in determining willingness to pay a higher monthly water bill. This survey has compared two values: the value of WTP and the cost of averting expenditure (CAE). My results showed that WTP is not always greater than CAE. Empirical results have policy implications on drinking water price strategies and drinking water related projects investment in Vietnam. Policy-makers or planners should consider income, gender, level of education, existing water sources, lifestyles, and locale when making drinking water price strategies and water related investment.
Zip file contains dataset.
Keywords: WTP; averting expenditure cost; CVM; households; safe drinking water; Vietnam